Age‐wise examination of the association of obesity based on body mass index and waist circumference with metabolic diseases in comprehensive health checkup participants - Yuiko Yamamoto; Kentaro Ikeue; Megumi Kanasaki; Hajime Yamakage; Noriko Satoh‐Asahara; Izuru Masuda; Kojiro Ishii (Wiley, 2024)
Abstract Aim Body mass index and waist circumference are used for obesity diagnosis and screening of visceral fat; however, their evidence in older adults is insufficient. This study investigated the age‐specific association of body mass index and waist circumference with metabolic diseases, assessing their applicability as diagnostic criteria for individuals aged ≥65 years. Methods Analysis included 46,324 individuals aged ≥18 years, categorized into five age groups: 18-44, 45-54, 55-64, 65-74, and ≥75 years. Logistic regression analyses identified associations between obesity and metabolic diseases, stratified by age and sex. Results Men with obesity based on body mass index had a significantly high risk of hypertension, diabetes mellitus, and dyslipidemia across all age groups (all, p < 0.05). Obesity based on waist circumference was significantly positively associated with all metabolic diseases (all, p < 0.05). Women with obesity based on body mass index and waist circumference had a significantly high risk of all metabolic diseases across all age groups (all, p < 0.05), except for diabetes mellitus in individuals aged ≥75 years. Conclusions Participants with obesity based on body mass index and waist circumference exhibited a high risk of hypertension, diabetes mellitus, and dyslipidemia among those aged 18-74 years and men aged ≥75 years. This study contributes to the early prevention and control of metabolic diseases.